A theoretical model for preventing marine litter behaviour: an empirical evidence from Singapore - Chen, Liren (2024)
Marine litter pollution has been an emerging environmental problem and arousing extensive attentions from both the academia and the public in recent years. The improperly disposed domestic refuse has been proven to be a major source of the marine litter, which can be effectively prevented through scientific waste management and citizens' daily pro-environmental behaviour. This study aims to investigates Singapore citizens’ intention of avoiding marine litter based on an extended theory of planned behaviour (TPB), incorporating the cognitive constructs as precursors and the irrational constructs as mediators. An online survey was performed targeting Singapore citizens to collect data, and 417 valid responses were analysed using structural equation modelling. The results reveal that environmental knowledge possess significant indirect effect to intention, and concern can act as a predictor of behaviour intention by influencing TPB constructs. Behaviour intention is most influenced by perceived behaviour control, while subjective norm has less constraining force. The irrational factors influence behaviour intention through both direct and indirect paths, habit exerts significant effect to behaviour patterns, while positive affection has greater effect size than negative affection. Previous research regarding marine litter preventing behaviour focus on tourists and consumers, while the survey object of this study is daily behaviour of citizens. The proposed theoretical model extends the traditional TPB by incorporating the cognitive and irrational factors, and offers deeper insights into the process of behaviour change. Besides, the findings also provide implications for government agencies in the field of marine litter control and waste management.